Play with functions 5

Calculus Level 5

Let f : R + R f: \mathbb {R^+\to R} be an infinitely differentiable function with f ( 1 ) = 3 f(1) = 3 and satisfying

1 x y f ( t ) d t = y 1 x f ( t ) d t + x 1 y f ( t ) d t \large \int _{ 1 }^{ xy }f(t) \ dt = y\int _{ 1 }^{ x } f( t) \ dt + x\int _{ 1 }^{ y } f( t) \ dt

Find f ( e ) f(e) .

Also try Play with functions 2


The answer is 6.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

1 solution

Prakhar Gupta
Feb 6, 2015

Let's define a function g ( x ) g(x) . 1 x f ( t ) d t = g ( x ) \int_{1}^{x}f(t)dt = g(x) So the given equation becomes:- g ( x y ) = y g ( x ) + x g ( y ) g(xy)= yg(x) + x g(y) Put y = 2 y=2 . g ( 2 x ) = 2 g ( x ) + x g ( 2 ) g(2x) = 2g(x) + x g(2) Differentiate the above equation. 2 g ( 2 x ) = 2 g ( x ) + g ( 2 ) ( 1 ) 2g'(2x) = 2g'(x) + g(2) \ldots (1) From the definition of g ( x ) g(x) and Newton-Leibniz rule, we have:- g ( x ) = f ( x ) g'(x) = f(x) From (1):- 2 f ( 2 x ) = 2 f ( x ) + g ( 2 ) 2f(2x) = 2 f(x)+ g(2) f ( 2 x ) = f ( x ) + g ( 2 ) 2 ( 2 ) f(2x) = f(x)+ \dfrac{g(2)}{2} \ldots (2) Put x = 2 0 , 2 1 , 2 2 2 n 1 x = 2^{0} , 2^{1}, 2^{2} \ldots 2^{n-1} in equation ( 2 ) (2) and add all the equations. We will get:- f ( 2 n ) = f ( 1 ) + n g ( 2 ) 2 f(2^{n}) = f(1) + \dfrac{n g(2)}{2} . Make the following substitution:- 2 n = x 2^{n} = x n ln 2 = ln x n\ln2 = \ln x n = ln x ln 2 n= \dfrac{\ln x}{\ln2} Hence our equation becomes:- f ( x ) = f ( 1 ) + g ( 2 ) ln x 2 ln 2 ( 3 ) f(x) = f(1) + \dfrac{ g(2) \ln x}{2\ln2} \ldots (3) From the definition of g ( x ) g(x) , we can write:- 1 2 f ( t ) d t = g ( 2 ) \int_{1}^{2} f(t)dt = g(2) 1 2 ( f ( 1 ) + g ( 2 ) ln t 2 ln 2 ) d t = g ( 2 ) \int_{1}^{2} \Bigg( f(1) + \dfrac{ g(2) \ln t}{2\ln2} \Bigg) dt = g(2) Solving above integral and then solving for g ( 2 ) g(2) we have:- g ( 2 ) = 2 ln 2 f ( 1 ) g(2) = 2\ln2 f(1) From equation ( 3 ) (3) :- f ( x ) = f ( 1 ) + ln x f ( 1 ) f(x) = f(1)+\ln xf(1) f ( x ) = f ( 1 ) ( 1 + ln x ) f(x) = f(1) ( 1+ \ln x) Put x = e x= e . f ( e ) = 2 f ( 1 ) \boxed{f(e) = 2f(1)}

I really loved this problem. Very beautiful problem.

Prakhar Gupta - 6 years, 4 months ago

Log in to reply

Nice solution great!!!!!!!!!!!

abdulmuttalib lokhandwala - 6 years, 4 months ago

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...